Buddhist Education Teachers of Elementary School’ Perception towards the Implementation of Learning Tool Development Training - Santi, Metta; Dwikurnaningsih, Yari (LPPM Undiksha, 2022)
Training is one alternative that is still trusted and used as an effort to improve the quality of teachers. This study aims to determine the perception of Buddhist education teachers at the elementary school level in Pesawaran Regency on the implementation of training in the development of learning tools. This study used a mixed-method, explanatory sequential mixed-method research design. All teachers of Buddhist education at the elementary school level were the subjects of this study. The instruments used in this study were questionnaires and interviews. The questionnaire consisted of 37 statements and the interview consisted of 27 questions. Before testing the questionnaire, the validity and reliability tests were carried out using the SPSS statistic 25 program. The findings in this study revealed that perceptions were quite good in online and face-to-face training for Buddhist education teachers. Objectives, implementation, methods, costs, media and evaluation get a percentage of <40%. Collaborating the two trainings is a way that can be used to minimize deficiencies and maximize both trainings.